Determinants of German direct investment in CEE countries - Niklas Becker; Andrzej Cieślik (Journal of Risk and Financial Management, 2020)
This paper studies the determinants of German direct investment in the Central and Eastern European countries during the period 1996-2016 using the augmented Knowledge Capital model to identify the main reasons for foreign direct investment (FDI). The empirical results show increasing multinational enterprise (MNE) activity with growth in country-size and with growing similarities of countries, which supports the horizontal reason for FDI; while the difference in the share of skilled labor force associated with the vertical reason has no effect. Furthermore, the estimation results show unimportance of trade costs to the foreign market and the significance of the distance between source and host countries.
Keywords: 330; foreign direct investment; Central and Eastern Europe (CEE) countries; German MNEs; knowledge capital model